Healthcare access dimensions and uterine cancer survival: a national cancer database study - Anastasio, Mary Katherine; Gupta, Anjali; Akinyemiju, Tomi F.; Previs, Rebecca A. (Frontiers in Oncology, 2023)
Objective: Disparities exist throughout diagnosis, treatment, and survival for Black patients with uterine cancer. There is limited data on how several healthcare access (HCA) dimensions contribute to these disparities in patients with advanced stage uterine cancer. Methods: Using the National Cancer Database (NCDB), we identified patients aged 40-89 years with Stage III-IV uterine cancer between 2004-2015 who received chemotherapy and/or radiotherapy. Race/ethnicity were classified as non-Hispanic (NH)-Black, Hispanic, and NH-White. Variables defined in the NCDB were used to assess HCA affordability, availability, and accessibility. Kaplan-Meier estimates, log-rank test, and multivariable Cox proportional hazards models were used to analyze overall survival. Results: Of 43,134 patients, 78.8% of the cohort identified as NH-White, 15.3% NH-Black, and 5.9% Hispanic. NH-Black patients were the most likely to have type II (75.6% vs. 53.9% and 55.4%) and stage IV (40.8% vs. 30.7% and 32.3%) disease compared to NH-White and Hispanic patients. NH-Black patients were more likely than NH-White and Hispanic patients to have government funded insurance (58.6% vs. 50.3% and 50.4%), live in low-income areas (46.4% vs. 14.2% and 29.9%), and receive only chemotherapy (53.5% vs. 43.1% and 46.2%). Having private insurance and receiving treatment at an academic facility were positive predictors of survival. NH-Black patients had worse survival than NH-White patients after adjusting for clinical characteristics and healthcare access dimensions (HR 1.29; 95% CI 1.24, 1.34). Conclusions: While HCA affordability and availability predicted survival in patients with advanced stage uterine cancer, additional factors contribute to racial disparities. Compared to NH-White patients, NH-Black patients had more aggressive disease, received only chemotherapy rather than combined therapy, and had worse survival regardless of cancer subtype. Additional dimensions of healthcare access must be explored to remedy uterine cancer disparities.